Electronic and optical properties of multifunctional R3c AFeO3 (A = Sc or In) compounds: Insights into their potential for photovoltaic applications. (January 2022) - Souza, J.S.; Alves, L.L.; Lima, A.F.; Lalic, M.V.
Abstract: Employing the spin density functional theory calculations we have investigated the electronic and optical properties of multifunctional R3c AFeO3 (A = Sc or In) compounds in order to understand their potential for photovoltaic applications. Due to a lack of experimental information about these properties, we used a well-documented, isostructural BiFeO3 compound as a benchmark to be compared with. To approximate the exchange and correlation effects, we employed the local spin density approximation (LSDA) including effective Hubbard U correction (Ueff  = 6.0 eV) for the Fe 3d band. Based on this methodology, we found that the ScFeO3 and InFeO3 exhibit direct energy band gaps of 3.0 eV and 2.6 eV, respectively, and absorb visible light in the extreme part of the visible solar spectrum. The calculated effective masses (m*) are found to be comparable to those of the commercial conventional semiconductors (m* ≤ 0.5 m0 ). Energies of dissociation of the excitons are estimated to be very low (<2.0 meV), well below the energy of thermal excitation (KB T ~ 26 meV). All of these properties are comparable to those of the BiFeO3, which is already utilized in photovoltaic applications. Thus, we conclude that the ScFeO3 and InFeO3 also have a great potential to be used for the same purpose. Highlights: Magnetoelectric ScFeO3 and InFeO3 were treated in the frame of DFT. Band gaps: 3.0 eV (ScFeO3 ) and 2.6 eV (InFeO3 ) are found to be direct. Effective masses of charge carriers are found to be light. Binding energy of photo-generated excitons is estimated to be very low. Both compounds exhibit potential for photovoltaic applications.